1977
DOI: 10.1093/bja/49.11.1139
|View full text |Cite
|
Sign up to set email alerts
|

ANALGESIA AFTER OPERATION: A controlled comparison of meptazinol, pentazocine and pethidine

Abstract: In a double-blind investigation of the efficacy on pain following abdominal or orthopaedic surgery, meptazinol 100 mg, a new hexahydroazepine derivative, was found to be equipotent with pentazocine 60 mg and pethidine 100 mg when given i.m. Analgesia was maximal 30-60 min after injection and was still present at the end of 2 h. The duration of action of meptazinol was estimated to be 4 h. Meptazinol produced less sedation and a greater sparing of lung function tests than did pethidine and pentazocine. When mep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
1

Year Published

1980
1980
1994
1994

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 8 publications
3
13
1
Order By: Relevance
“…Meptazinol was found to produce a negligible effect on respiration in animals when compared with opiates and pentazocine (Stephens et al, 1978). Observations in normal human volunteers (Jordan et al, 1979) and patients (Verschraegen, 1976;Paymaster, 1977) confirm this favourable result. Meptazinol undergoes hepatic glucuronidation as opposed to N-demethylation and would not be expected to be metabolised as differently in mother and infant as is pethidine.…”
mentioning
confidence: 91%
“…Meptazinol was found to produce a negligible effect on respiration in animals when compared with opiates and pentazocine (Stephens et al, 1978). Observations in normal human volunteers (Jordan et al, 1979) and patients (Verschraegen, 1976;Paymaster, 1977) confirm this favourable result. Meptazinol undergoes hepatic glucuronidation as opposed to N-demethylation and would not be expected to be metabolised as differently in mother and infant as is pethidine.…”
mentioning
confidence: 91%
“…There was a trend towards an increased volume of distribution in the patients with liver disease but this failed to reach statistical significance (control=303±32 1; NCLD=385+43 1; cirrhotic=402±36 1). There was no differences in the total plasma clearance of meptazinol between the groups (control=83± 10 following an oral dose of200 mg ofmeptazinol in control (n= 7), non-cirrhotic liver disease (NCLD) (n=8) and cirrhoticpatients (n=8). 12 …”
Section: Meptazinoi Kineticsmentioning
confidence: 97%
“…Meptazinol is a novel benzomorphan compound with partial opiate-antagonist properties which has been shown to be equivalent in analgesic potency at a dose of 100 mg to pethidine 100 mg (Paymaster, 1977; A. Hedges (personal communication); M. B. A. Jackson and P. J. Robson (personal communication), papaveretum 20 mg (Moyer, Miller and Aldridge, 1979) and pentazocine 60 mg (Paymaster, 1977), all drugs given i.m.…”
Section: Introductionmentioning
confidence: 99%
“…A. Jackson and P. J. Robson (personal communication), papaveretum 20 mg (Moyer, Miller and Aldridge, 1979) and pentazocine 60 mg (Paymaster, 1977), all drugs given i.m. It is free from anti-5-hydroxytryptamine and anti-cholinergic activity and in clinical trial has shown a low incidence of CNS side effects.…”
Section: Introductionmentioning
confidence: 99%